1999
DOI: 10.1097/00001888-199903000-00020
|View full text |Cite
|
Sign up to set email alerts
|

Part-time residency training in internal medicine

Abstract: This part-time residency curriculum provided a highly useful program track for a group of internal medicine residents with concomitant obligations, allowing them to complete their training in an uninterrupted fashion. The part-time structure did not adversely affect clinical competence and may have fostered humanistic attributes. The authors believe that this form of curriculum deserves wider consideration in residency training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…[32][33][34][35][36][37] Saalwachter et al studied 4308 medical students, residents, and practicing surgeons to assess their interest in an extension of residency training in exchange for ≥1 year of "part-time" training (40-80 hours per week). 35 Among medical students, 36% of women and 24% of men reported an increased interest in a surgical career if this option was available.…”
Section: Discussionmentioning
confidence: 99%
“…[32][33][34][35][36][37] Saalwachter et al studied 4308 medical students, residents, and practicing surgeons to assess their interest in an extension of residency training in exchange for ≥1 year of "part-time" training (40-80 hours per week). 35 Among medical students, 36% of women and 24% of men reported an increased interest in a surgical career if this option was available.…”
Section: Discussionmentioning
confidence: 99%
“…Research on trainee outcomes with these models, although limited, has shown clearly that job sharing results in high levels of satisfaction and enthusiasm, less tiredness and no evidence of compromised continuity of care 6 . A study of part‐time trainees found that they scored significantly better than their full‐time colleagues on humanistic skills 7 . However, there is a lack of information specifically on educational outcomes, and it is not known whether a minimum level of training is required to maintain skills, or whether gaining of competencies is affected by breaks in the otherwise immersive training experience.…”
Section: How Can Physician Training Be Made More Flexible?mentioning
confidence: 99%
“…20 In a survey on part-time residency training, it was found that part-time residency students had better performance than fulltime students. 13 In the same study, part-time trainees were found to be successful in humanistic skills. The part time residency in these examples means not being obliged to study or work in health services all the work day long but have the rest of the day off for personal purposes.…”
Section: Resultsmentioning
confidence: 89%
“…9 It is stated that this trend is also rising worldwide including Europe, North America, Asia, Australia and Africa. [9][10][11][12][13][14][15][16][17][18][19] In Switzerland, 44 specialist degrees can be obtained with part-time courses. 10 Increased interest in parttime training is linked to feminization in medical education.…”
Section: Resultsmentioning
confidence: 99%